Spin Coater Design with PID Algorithm Using Polynomial Regression Approach and Bias Tuning for TiO2 Deposition Process - Andika, Geo Surya; Sofyan, Nofrijon; Dhaneswara, Donanta; Yuwono, Akhmad Herman (Journal of Materials Exploration and Findings, 2025)
The thin-film deposition technique using spin coating offers a cost-effective alternative to Chemical Vapor Deposition (CVD) and Physical Vapor Deposition (PVD). The spin-coating process requires precise control of the motor drive system to ensure that the rotational speed, measured in rotations per minute (RPM), aligns with the set point and remains stable. This study presents the design and development of a spin coater prototype to achieve uniform thin-film deposition. The control method employed utilizes a Proportional-Integral-Derivative (PID) algorithm, incorporating a polynomial approach with bias tuning. The PID control was chosen to achieve stable operation in a non-linear system. The performance of the non-linear PID control system is compared with an open-loop control system by evaluating the overshoot behavior. In the first experiment, a proximity sensor was tested to measure the spin coater motor's speed in an open-loop control configuration. The performance was evaluated using Mean Absolute Error (MAE) and Mean Absolute Percentage Error (MAPE) metrics, with results showing an MAE of 1358.6 RPM and a MAPE of 23.13% compared to a tachometer. In the second experiment, step-response testing was conducted using a closed-loop PID control system with a polynomial approach and bias tuning. Compared to the open-loop system, the closed-loop PID controller reduced overshoot to less than 3%. The RPM deviation between the spin coater and the tachometer was limited to range, approaching ideal conditions. The closed-loop control was tested within the 5000–9000 RPM range, where stable RPM regulation resulted in more uniform TiO2 thin-film distribution on glass substrates. This study highlights the effectiveness of closed-loop PID control in achieving precise rotational control, which is essential for enhancing the quality of thin-film deposition.